1996
DOI: 10.1113/jphysiol.1996.sp021181
|View full text |Cite
|
Sign up to set email alerts
|

Properties of presympathetic neurones in the rostral ventrolateral medulla in the rat: an intracellular study "in vivo'.

Abstract: 1. Intracellular recordings were made in pentobarbitone-anaesthetized rats from sixty-eight neurones located in the rostral ventrolateral medulla (RVLM), which responded with inhibition (latency, 33-6 + 9-3 ms) after stimulation of the aortic depressor nerve with short bursts of pulses. This inhibition was due to chloride-and voltage-dependent IPSPs. 2. Seventeen neurones could be excited antidromically after stimulation in the T2 spinal segment (conduction velocity, 1 9-8-5 m s-1) and were classified as RVLM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
103
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 35 publications
5
103
0
1
Order By: Relevance
“…The ongoing activity of these neurons resulted of synaptic inputs, with individual action potentials usually preceded by identifiable fast EPSPs (Lipski et al 1996). These findings are in agreement with the network hypothesis of the generation of sympathetic vasomotor tone proposed by Barman and Gebber (1987).…”
Section: The Rostral Ventrolateral Medulla and The Generation Of The supporting
confidence: 81%
See 2 more Smart Citations
“…The ongoing activity of these neurons resulted of synaptic inputs, with individual action potentials usually preceded by identifiable fast EPSPs (Lipski et al 1996). These findings are in agreement with the network hypothesis of the generation of sympathetic vasomotor tone proposed by Barman and Gebber (1987).…”
Section: The Rostral Ventrolateral Medulla and The Generation Of The supporting
confidence: 81%
“…As proposed by Lipski (Lipski et al 1996), it is possible that, under normal conditions, RVLM premotor neuron activity is determined by the balance between excitatory and inhibitory synaptic inputs, including amino acid excita-tory mechanisms. However, under special conditions, such as hypertension, an imbalance between these inputs, resulting in an increased excitatory activity within the RVLM, may enhance the tonic activity of RVLM neurons.…”
Section: The Rostral Ventrolateral Medulla and The Generation Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…This negative result could have been due to technical deficiencies, since R-type neurons tend to be smaller than I-type neurons, as reported by Oshima et al (2000), for the brain stem/spinal cord preparation. The small-sized neurons in the study of Lipski et al (1996) could have been preferentially damaged, because even some of the larger (I-type) neurons in that study showed signs of damage (Fig. 8C in Lipski et al 1996), thus indicating that the technique used was not suitable for penetration of the smaller R-type neurons in the RVLM.…”
Section: Types Of Neuronal Dischargementioning
confidence: 93%
“…Another group of investigators (Lipski et al 1996), using intracellular recordings in the in vivo rat preparation, has reported conflicting results: they could not find regularly firing bulbospinal barosensitive neurons. This negative result could have been due to technical deficiencies, since R-type neurons tend to be smaller than I-type neurons, as reported by Oshima et al (2000), for the brain stem/spinal cord preparation.…”
Section: Types Of Neuronal Dischargementioning
confidence: 99%